Pola Komunikasi Konten Kreator Abdul Aziz Dalam Mensosialisasikan Bahasa Isyarat pada Akun Instagram @pikiping - Fatmawati, Rosiana Fani; Riyanto, Buddy; Muadz, Muadz (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Slamet Riyadi Surakarta, 2024)
This research aims to study the communication patterns used by Abdul Aziz in socializing sign language on his Instagram account @pikiping. The research method used in this research is descriptive qualitative which presents a narative gaìgaìraìn about a situation such as the issue or phenomenon of life from Instagram posts @pikiping. The data is collected through interviews with Abdul Aziz, collaboration partner and 2 followers of the @pikiping account and obtained from documents in the form of Abdul Aziz's content archive. The theory used is a two-way communication pattern, using verbal and non-verbal forms of language as well as new media theory. The results of this research show how the communication pattern implemented by Abdul ​​Aziz has been effective and interactive because it has influenced his followers to become more interested and eager to know about the information regarding the information and facts, also deaf culture or the lives of deaf people. The followers give him opinions and suggestions which is related to @pikiping's Instagram content. However, Abdul Aziz continues to maintain content containing deaf culture and sign language, always increasing interaction with his followers and the community and developing content in accordance with issues developing in wider society.